DETERMINAN AUDIT DELAY PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA TAHUN 2017-2019 - Arieta Nura Aisha; Anis Chariri (Diponegoro Journal of Accounting, 2022)
This research aims to analyze the determinants of audit delay in manufacturing companies in Indonesia. The variables used in the test are audit mission complexity, audit opinion, KAP reputation, company size, financial debt, and profitability as independent variables, and audit delay as dependent variable.The population in this research are manufacturing companies listed on the Indonesia Stock Exchange with an observation period of 2017-2019. Sampling based on purposive sampling method that follows certain criteria(s). The sample used in this study were 297 companies. Multiple linear regression analysis is an analytical method used in research.The results showed that the KAP reputation, company size, and profitability have a negative significant effect on audit delay. Financial debt has a positive significant effect on audit delay. Meanwhile, audit mission complexity and audit opinion have a negative but not significant effect on audit delay